Cellular Phenotypic Analysis of Macrophage Activation Unveils Kinetic Responses of Agents Targeting Phosphorylation. (January 2017) - Cao, Qian; Yao, Junlin; Li, Heyuan; Tao, Bo; Cai, Yibo; Xiao, Peng; Cheng, Hongqiang; Ke, Yuehai
Macrophages are highly plastic cells, which serve as sentinels of the host immune system due to their ability to recognize and respond to microbial products rapidly and dynamically. Appropriate regulation of macrophage activation is essential for pathogen clearance or preventing autoimmune diseases. However, regularly used endpoint assays for analyzing macrophage functions have the limitations of being static and non–high throughput. In this study, we introduced a real-time and convenient method based on changes in cellular impedance that are detected by microelectronic biosensors. This new method can record the time/dose-dependent cell response profiles (TCRPs) of macrophages in real time and generates physiologically relevant data. The TCRPs generated from classically interferon-γ/lipopolysaccharide-activated macrophages showed considerable consistency with the data generated from standard endpoint assays. We further explored this approach by using it for global screening of a library of protein tyrosine kinase/phosphatase (PTK/PTP) inhibitors to investigate their impact on macrophage activation. Collectively, our findings suggest that the cellular impedance-based assay provides a promising approach for dynamically monitoring macrophage functions in a convenient and high-throughput manner.